How to write poems - Magee, Wes, 1939- (Laguna Hills, CA : QEB, 2007)
Contains tips and activities to teach young learners how to write poetry.
Includes index.
4.9
3-6
Keywords: Poetry -- Authorship -- Juvenile literature; Poetry -- Authorship; Poetics; Poetry -- Authorship